Medical genetic study of population in rural districts of Buryatia Republic - L. I. Minaycheva; L. P. Nazarenko; Ye. R. Yeryomina; V. B. Tsyrenova; O. A. Salyukova; S. V. Fadyushina; V. B. Ayushina (Бюллетень сибирской медицины, 2009)
Medical-genetic study of the population of 5 rural districts of Buryatia Republic has been performed. The number of investigative population was 114,6 thousands people. The 23, 9 and 8 nosological forms of autosomal dominant, autosomal recessive and Xlinked diseases were revealed, respectively. The hereditary pathology spectrum and the features of prevalence in the studied population were described.